Thematic analysis of stakeholder perceptions for co-creative healthcare XR resource design and development; traversing a minefield of opportunities - Antoniou, Panagiotis Evaggelos; Varella, Annita; Pickering, James D.; Chatzimallis, Charalambos; Moumtzi, Vassiliki; Bamidis, Panagiotis D. (Frontiers in Digital Health, 2024)
The expansive curricular volume of healthcare education makes a necessity the incorporation of innovative methods and immersive media in it. The core challenge in such approaches is the timely development of relevant immersive content such as Virtual, Augmented or Mixed Reality (VR/AR/MR) resources for healthcare topics. There is currently significant interest in the use of cocreative methods for streamlining immersive content development. A core research pursuit in this translational research field is the formulation of evidence-based, optimized workflows that streamline immersive content creation allowing for rapid expansion of innovative educational approaches in healthcare curricula. The purpose of this paper is to aggregate the perceptions of healthcare technologists and educators who participated in a series of co-creation sessions in order to elicit their best practice insights for design and development of XR educational resources using co-creative methods. According to our thematic analysis, findings of the qualitative study demonstrated that a rigorous organizational approach is required to maintain a constructive exchange of information and to keep the design process alive for both content and technical experts. In addition, rapid prototype and display of co-created features can empower their contributions and help them design more efficiently. Co-creative content production can benefit from adaption of existing frameworks and lightweight authoring environments that can facilitate generalized XR content development use cases.